"A ship loaded with honey:" assessing the honey trade in the Crown of Aragon, fifteenth to sixteenth centuries. Issue 2 (4th May 2022) - Sales i Favà, Lluís
ABSTRACT: Honey, a staple product in premodern societies, has been too often overlooked by historical research. The present article focuses on a moment when the honey trade was in decline in the Crown of Aragon (c . 1440-1570). After the heyday of exports to the Levant of the late fourteenth century, supply was now mostly reserved to domestic consumption. Through the analysis of different fiscal sources from Valencia and Barcelona, this study addresses the principal supplying regions in the Crown of Aragon, the actors involved, and the means of transport in the honey market.